Global health governance and geopolitics: How Germany can contribute to a new global health architecture after Covid-19 amid growing geopolitical tensions - Michael Bayerlein; Pedro A. Villarreal (Stiftung Wissenschaft und Politik (SWP), 2023)
The development of a new global health architecture in the wake of Covid-19 will require important decisions to be made, especially when it comes to negotiating a pandemic accord and creating robust supply chains. Against the backdrop of their systemic rivalry, the US and China view global health policy as a field of geopolitical competition. This jeopardises the implementation of lessons learned from the Covid‑19 pandemic, not to mention global health in general. The question for Germany is to what extent it needs to adapt its multilateral approach to global health in order to respond to increasing geopolitical tensions. To this end, Germany should develop independent leverage to shape global health policy while also being a reliable, multilateral partner to all countries willing to improve in this field
Keywords: 320; global health architecture; Covid-19; systemic rivalry US and China; pandemic prevention; pandemic accord; World Health Organization (WHO); Emergency Plan for AIDS Relief (PEPFAR)